2020
DOI: 10.1016/j.healthplace.2019.102262
|View full text |Cite
|
Sign up to set email alerts
|

Urban regeneration and mental health: Investigating the effects of an area-based intervention using a modified intention to treat analysis with alternative outcome measures

Abstract: Urban regeneration and mental health: investigating the effects of an area-based intervention using a modified intention to treat analysis with alternative outcome measures. Health and Place, 61, 102262.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Overall, we found mixed results, in that only some of the interventions (comprehensive or focused green and transport infrastructure) were associated with increased residential satisfaction, quality of life, and wellbeing for low-income residents and women. This weak evidence is partially in line with what was found in previous investigations of urban regeneration and mental health [20][21][22]. In their systematic review of controlled studies, for instance, Moore et al [22] identified small improvements in quality of life or social integration associated with green infrastructure interventions but no evidence of benefits associated with large regeneration projects.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Overall, we found mixed results, in that only some of the interventions (comprehensive or focused green and transport infrastructure) were associated with increased residential satisfaction, quality of life, and wellbeing for low-income residents and women. This weak evidence is partially in line with what was found in previous investigations of urban regeneration and mental health [20][21][22]. In their systematic review of controlled studies, for instance, Moore et al [22] identified small improvements in quality of life or social integration associated with green infrastructure interventions but no evidence of benefits associated with large regeneration projects.…”
Section: Discussionsupporting
confidence: 71%
“…Since the publication of Montgomery's Happy City book [19], there have been increasing attempts to develop ways to measure the link between urban development and happiness [12]; however, there is mixed evidence on the association between urban transformation and psychological wellbeing. For instance, a study in Spain found that urban renewal projects focused on active travel and inclusive public spaces benefited residents' mental wellbeing [20], whereas another study in the UK observed no sizeable psychological benefits associated with housing regeneration projects [21]. Similarly, a recent systematic review of the impact of urban interventions on mental health [22], found limited and weak evidence for a positive impact of improvements to green infrastructure on quality of life and social isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who develop mental health problems may experience feelings of depression, hopelessness, failure, fear, loneliness, and meaninglessness [ 77 ]. Therefore, for the second dimension, mental health, respondents were asked six questions: “How often do you feel depressed (variable named depression)?”, “How often do you feel like there is no hope (variable named hopelessness)?”, “How often do you feel you have failed (variable named failure)?”, “How often do you experience fear (variable named fear)?”, “How often do you feel lonely (variable named loneliness)?”, and “How often do you feel life is meaningless (variable named meaninglessness)?” The answers were coded from “1” (very low frequency) to “4” (very high frequency), which meant that the individual mental health status was ranked from good to poor [ 78 , 79 ].…”
Section: Methodsmentioning
confidence: 99%
“…None of the seven local environment improvement interventions [ 178 , 179 , 180 , 181 , 182 , 183 , 184 ] included a control group. Five studies examined if wellbeing changed over the course of the intervention, with only two reporting a significant increase [ 182 , 183 ].…”
Section: Resultsmentioning
confidence: 99%